N‐H Stretching Modes Around 3300 Wavenumber From Peptide Backbones Observed by Chiral Sum Frequency Generation Vibrational Spectroscopy. Issue 9 (7th March 2014) - Fu, Li; Wang, Zhuguang; Yan, Elsa C. Y.
ABSTRACT We present a detailed analysis of the molecular origin of the chiral sum frequency generation (SFG) signals of proteins and peptides at interfaces in the N‐H stretching vibrational region. The N‐H stretching can be a probe for investigating structural and functional properties of proteins, but remains technically difficult to analyze due to the overlapping with the O‐H stretching of water molecules. Chiral SFG spectroscopy offers unique tools to study the N‐H stretching from proteins at interfaces without interference from the water background. However, the molecular origin of the N‐H stretching signals of proteins is still unclear. This work provides a justification of the origin of chiral N‐H signals by analyzing the vibrational frequencies, examining chiral SFG theory, studying proton (hydrogen/deuterium) exchange kinetics, and performing optical control experiments. The results demonstrate that the chiral N‐H stretching signals at ~3300 cm‐1 originate from the amide group of the protein backbones. This chiral N‐H stretching signal offers an in situ, real‐time, and background‐free probe for interrogating the protein structures and dynamics at interfaces at the molecular level. Chirality 26:161–164, 2014. © 2014 Wiley Periodicals, Inc.